Crown fracture: Failure load, stress distribution, and fractographic analysis - Campos, Roberto E.; Soares, Paulo V.; Versluis, Antheunis; Junior, Osmir Batista de O. [UNESP]; Ambrosano, Glaucia M. B.; Nunes, Isabella Ferola (Elsevier B.V., 2015)
Statement of problem. The outcomes from load-to-failure tests may not be applicable to clinical situations. Purpose. The purpose of this study was to critically evaluate the efficacy of load-to-failure tests in the investigation of the fracture load and pattern of metal-free crowns. Material and methods. Four groups were formed from 128 bovine roots restored with metal posts, resin cores, and feldspathic, leucite, or lithium disilicate ceramic systems or polymer crowns. Each group was divided into 4 (n=8) according to the cement: zinc phosphate, self-adhesive resin, autopolymerizing resin, and glass ionomer. Mean fracture loads from compressive tests were submitted to ANOVA and Tukey HSD test. Finite element and fractographic analyses were performed and associated with the fracture load and pattern. Results. Significantly higher fracture load values were obtained for the lithium disilicate ceramic, but finite element and fractographic analyses showed that the cement effect could not be determined. The finite element analysis showed the cement likely affected the fracture pattern, confirmed that stresses in the cements were little affected by the crown materials, and found that the stressed conditions were lowest in the lithium disilicate compared with other crowns for all cement combinations. The stressed conditions in the crowns depended more on the adhesive properties than on the elastic modulus of the cement materials. The level of the stressed condition in the crowns at the occlusal surface was about the same or higher than along their cement interface, consistent with the fractography, which indicated fractures starting at the load point. Higher stress levels in the crowns corresponded with a lower number of catastrophic fractures, and higher stresses in the cements seemed to reduce the number of catastrophic fracture patterns. The highest stressed conditions occurred along the occlusal surface for crown materials with a low elastic modulus or in combination with adhesive cements. Conclusions. The method used was not appropriate either for investigating the crowns' fracture load and pattern or for stating the role of the cements within the crown-cement-tooth interaction.